Indole microbial intestinal metabolites expand the repertoire of ligands and agonists of the human pregnane X receptor - Illés, Peter; Krasulová, Kristýna; Vyhlídalová, Barbora; Poulíková, Karolína; Marcalíková, Adéla; Pečinková, Petra; Sirotová, Natália; Vrzal, Radim; Mani, Sridhar; Dvořák, Zdeněk (Toxicology letters, 2020)
The interplays between the metabolic products of intestinal microbiota and the host signaling through xenobiotic receptors, including pregnane X receptor (PXR), are of growing interest, in the context of intestinal health and disease. A distinct class of microbial catabolites is formed from dietary tryptophan, having the indole scaffold in their core structure, which is a biologically active entity. In the current study, we examined a series of ten tryptophan microbial catabolites for their interactions with PXR signaling. Utilizing a reporter gene assay, we identified indole (IND) and indole-3-acetamide (IAD) as PXR agonists. IND and IAD induced PXR-regulated genes CYP3A4 and MDR1 in human intestinal cancer cells. Using time-resolved fluorescence resonance energy transfer, we show that IND (IC50 292 μM) and IAD (IC50 10 μM) are orthosteric ligands of PXR. Binding of PXR in its DNA response elements was enhanced by IND and IAD, as revealed by chromatin immunoprecipitation assay. We demonstrate that tryptophan microbial intestinal metabolites IND and IAD are ligands and agonists of human PXR. These findings are of particular importance in understanding the roles of microbial catabolites in human physiology and pathophysiology. Furthermore, these results are seminal in expanding potential drug repertoire through microbial metabolic mimicry.
Keywords: kyseliny indoloctové; Gastrointestinal Microbiome; Ligands; tryptofan; indoly; Pregnane X Receptor; Humans; ligandy; Indoles; Intestinal health; Protein Binding; střevní sliznice; cytochrom P-450 CYP3A; pregnanový X receptor; Tryptophan; lidé; ATP Binding Cassette Transporter, Subfamily B; reportérové geny; Cells, Cultured; Pregnane X receptor; transfekce; Microbial catabolism; Indole metabolites; Male; P-glykoproteiny; kultivované buňky; Genes, Reporter; vazba proteinů; nádorové buněčné linie; Cytochrome P-450 CYP3A; Transfection; Indoleacetic Acids; střevní mikroflóra; Cell Line, Tumor; mužské pohlaví; Intestinal Mucosa